Primary Diagnosis of Abnormal Urine via Auto Fluorescence Process - Al-Ani, Rana R. (Iraqi Journal of Laser, 2019)
The main objective of this study is to determine the suitable excitation wavelengths for urine components reaching to select the suitable lasers to execute the auto fluorescence due to their high intensities. The auto fluorescence was measured at 305, 325 and 350 nm excitation wavelengths for eleven urine samples which were also analyzed by conventional methods (chemical and microscopic examination). Data manipulation using Matlab package programming language showed that urine sample with normal chemical and biological components have emission peaks which are different from the infected urine samples. Despite the complexity of the composition of urine, fluorescence maxima can be observed. Most likely, the peaks observed do not result from a single fluorescent urinary metabolite, but depend on differences in urine component that is changed according the clinical situation of person